Representaciones musicales de lo francés en tonadillas dieciochescas - Aurèlia Pessarrodona (Mélanges de la Casa de Velázquez, 2016)
The chief object of this article is to discover what musical tools tonadilla composers in the second half of the 18th century might have used to represent French characters or characters associated with France, and generally the concept of Frenchness. It seeks to show a variety of dramatic/musical resources associated with the communicative power of music in the 18th century (especially topoi from ballet and dance music, and musical styles, forms and gestures) which go to make up a broad spectrum of Frenchness, a putative musical Francophony which did not necessarily have to be realistic but did have to be effective in the particular context of short comic plays.